2020
DOI: 10.1093/sleep/zsaa256
|View full text |Cite
|
Sign up to set email alerts
|

Blunted rest–activity rhythms link to higher body mass index and inflammatory markers in children

Abstract: Study Objectives Disturbances of rest-activity rhythms are associated with higher body mass index (BMI) in adults. Whether such relationship exists in children is unclear. We aimed to examine cross-sectional associations of rest-activity rhythm characteristics with BMI z-score and obesity-related inflammatory markers in school-age children. Methods Participants included 411 healthy children (mean±SD age 10.1±1.3 years, 50.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
5
24
0
Order By: Relevance
“…( 23 ) assessed the relationship between RAR stability (IS) and metabolic syndrome in the very elderly and found that low IS was associated with increased risk of BMI-based general obesity. Of note, these previous studies ( 22 , 23 , 38 , 40 ) evaluated RAR in relation to excess body fat only as expressed by BMI. Abdominal obesity, defined according to waist circumference or waist-to-hip ratio, is an indicator of visceral fat accumulation ( 41 ) and is a more powerful predictor of chronic diseases and premature death than BMI ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 23 ) assessed the relationship between RAR stability (IS) and metabolic syndrome in the very elderly and found that low IS was associated with increased risk of BMI-based general obesity. Of note, these previous studies ( 22 , 23 , 38 , 40 ) evaluated RAR in relation to excess body fat only as expressed by BMI. Abdominal obesity, defined according to waist circumference or waist-to-hip ratio, is an indicator of visceral fat accumulation ( 41 ) and is a more powerful predictor of chronic diseases and premature death than BMI ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing research links aberrant RAR patterns with poor health status, including greater risk of neurodegenerative disease (15)(16)(17), cardiometabolic disease (18) and mortality (19). Accelerometry-generated RAR metrics, including intradaily variability (IV, fragmentation of RAR) and interdaily stability (IS, day-to-day stability of RAR), have been associated with obesity in children, adolescents and in the elderly (20)(21)(22)(23). However, the relationship of RAR with obesity among general adults remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lower levels of PA may also affect circadian rhythmicity through decreased exposure to natural light, as increased PA is associated with greater outdoor light exposure [30][31][32]. These changes in behaviors may affect synchronization of circadian and circannual rhythms by affecting children's exposure to the light/dark cycle and contributing to a blunting of circadian rhythmicity which may contribute to accelerated weight gain [26,27,33]. According to the CCR Model children's sleep timing, duration, and variability, PA, and light exposure represent novel pathways which may differentially influence children's BMI during the school year and summer.…”
Section: Introductionmentioning
confidence: 99%
“…Specific pediatric diseases such as type 1 diabetes and prematurity can further induce internal misalignment and CV risk, creating a feedback loop between disease expression and circadian disruption (180,181). Obese children have lower-amplitude circadian rhythms, and even when BMI is controlled for, inflammation inversely correlates with the strength of the rhythm (182). Cardioprotective physiology, such as nocturnal blood pressure dipping, is also important in children yet appears to be disrupted by several pediatric disease states (183)(184)(185).…”
Section: Risk In Childrenmentioning
confidence: 99%